2021
DOI: 10.1186/s12884-021-03763-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intraperitoneal adhesions using striae gravidarum and scar characteristics in women undergoing repeated cesarean sections

Abstract: Background The current fact of increasing rates of cesarean deliveries is a catastrophe. Recurrent cesareans result in intraperitoneal adhesions that would lead to maternal morbidity during delivery. Great efforts are directed towards the prediction of intraperitoneal adhesions to provide the best care for laboring women. The aim of the current study was to evaluate the role of abdominal striae and cesarean scar characters in the prediction of intraperitoneal adhesions. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…Elprince et al reported a strong correlation between the abdominal scar index and abdominal striae in predicting intra-abdominal adhesions. It is contrary to the present study, possibly because the striae factor is not discussed in the present study (10).…”
Section: Discussioncontrasting
confidence: 99%
“…Elprince et al reported a strong correlation between the abdominal scar index and abdominal striae in predicting intra-abdominal adhesions. It is contrary to the present study, possibly because the striae factor is not discussed in the present study (10).…”
Section: Discussioncontrasting
confidence: 99%
“…Conflicting results are present regarding this issue. Some studies declared that hypopigmented and depressed scars were associated with dense intraperitoneal adhesions, 35,36 while others reported the contrary 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Some studies declared that hypopigmented and depressed scars were associated with dense intraperitoneal adhesions, 35,36 while others the contrary. 37,38 The effect of age on adhesion formation was unclear. Intestinal obstruction occurred after an appendectomy at age 20-39 and less than 60 years.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases as consequences of deep dermal defects appear hypoesthesia, hyperalgesia around the injured area, and functional limitations. 4,5 The normal wound healing process is a strictly controlled state of balance between the process of disintegration of the structure of the damaged tissue and the repair consisting in the synthesis and formation of a new, correct one. Mediators, blood cells, extracellular matrix cells, and parenchymal cells are involved in the process.…”
Section: F I G U R Ementioning
confidence: 99%
“…Despite recent advances in surgical techniques and scar therapies, there is no dependable strategy to manage postoperative adhesions. In many cases as consequences of deep dermal defects appear hypoesthesia, hyperalgesia around the injured area, and functional limitations 4,5 …”
Section: Introductionmentioning
confidence: 99%